Business cycle dynamics of a new Keynesian overlapping generations model with progressive income taxation - Burkhard Heer; Alfred Maußner (Center for Economic Studies and ifo Institute (CESifo), 2006)
In our dynamic optimizing sticky price model, agents are heterogeneous with regard to their age and their productivity. We find that the business cycle dynamics in the OLG model in response to both a technology shock and a monetary shock are similar, but not completely identical to those found in the corresponding representative-agent model. In particular, working hours in the OLG model decrease in response to a positive technological shock, since for young workers the income effect dominates the substitution effect. This is in line with the adverse effect of productivity shocks on employment found in structural vector autoregressions.
Keywords: E52; E32; D31; D58; E31; 330; fluctuations; unanticipated inflation; wealth distribution; income distribution; progressive income taxation; Calvo price staggering; Konjunkturtheorie; Ungleichgewichtstheorie; Overlapping Generations; Einkommensteuer; Steuerprogression; Produktivität; Geldpolitik; Schock; Theorie; USA